Optimalisasi Media Digital Sebagai Strategi Pemasaran UMKM di Desa Dauh Puri Kauh - Kevin Wijaya (PT. Adriani Mandiri Publisher, 2026)
In recent years, the use of social media for MSMEs to market their products has increased. Social media provides a broad and creative platform for selling, collaborating and being creative in the way of doing business. However, the use of social media as a means of marketing is very limited for some MSME actors. Therefore, the aim of this report is to assist Dauh Puri Kauh Traditional Village in the use of social media as a marketing strategy for MSMEs in the Dauh Puri Kauh Village area. The method of activity in this report is to create a program of Advancing Dauh Puri Kauh as a tool in this marketing strategy using social media. The results of this report prove that the use of social media as a marketing strategy for MSMEs in Dauh Puri Kauh Village is proven to be effective and more efficient in marketing these UMKM products.